Investigation on the Structural Evolutions during the Insertion of Aluminum Ions into Mo6S8 Chevrel Phase. Issue 6 (29th March 2016) - Lee, Boeun; Lee, Hae Ri; Yim, Taeeun; Kim, Jong Hak; Lee, June Gunn; Chung, Kyung Yoon; Cho, Byung Won; Oh, Si Hyoung
Abstract : Herein, we evaluate the detailed insertion mechanism of aluminum ions into the Mo6 S8 Chevrel phase in the 1-ethyl-3-methylimidazolium tetrachloroaluminate ionic liquid through combined structural and electrochemical characterization. This involves two-step two-phase insertion reactions, where the first and the second step account for 3/4 and 1/4 of the total reversible capacity, respectively. During the first step, aluminum ions occupy the inner ring sites in the Chevrel phase, forming AlMo6 S8 with a higher activation energy for cation diffusion. Subsequently, Al4/3 Mo6 S8 emerges as a discharge product during the second step, where one aluminum ion fills one outer ring site in every three AlMo6 S8 units. The diffusion coefficient for aluminum ions through the Chevrel phase was found much lower than that of lithium or magnesium ions, reflecting the difficulties in redistributing trivalent charge carried by each aluminum ion.